1998
DOI: 10.1046/j.1432-1327.1998.2540325.x
|View full text |Cite
|
Sign up to set email alerts
|

A family of flavoproteins in the domains Archaea and Bacteria

Abstract: A family of flavoproteins, called A-type flavoproteins, is described. It consists of 14 protein sequences of 385Ϫ597 amino acids in length, 7 from methanogens (domain: Archaea), 5 from phototrophic prokaryotes, one from Escherichia coli, and a partial sequence from the sulfate reducer Desulfovibrio gigas (domain : Bacteria). No similar sequence could be found in the domain Eucarya. All sequences show significant similarity over a 385Ϫ400 amino acid portion overlapping a recognizable flavodoxin signature starti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
87
0

Year Published

2000
2000
2013
2013

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(88 citation statements)
references
References 8 publications
1
87
0
Order By: Relevance
“…4) (42). It was suggested that these flavoproteins, which bind FAD and FMN at the same time in equimolecular amounts, might have evolved by the fusion of two flavin-binding domains located in the N-and C-terminus regions of the protein, showing different activities and functions (42).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…4) (42). It was suggested that these flavoproteins, which bind FAD and FMN at the same time in equimolecular amounts, might have evolved by the fusion of two flavin-binding domains located in the N-and C-terminus regions of the protein, showing different activities and functions (42).…”
Section: Resultsmentioning
confidence: 99%
“…4) (42). It was suggested that these flavoproteins, which bind FAD and FMN at the same time in equimolecular amounts, might have evolved by the fusion of two flavin-binding domains located in the N-and C-terminus regions of the protein, showing different activities and functions (42). The existence of a HpaC-like FMN binding domain in A-type flavoproteins suggests that a fusion between the reductase and oxygenase components of the enzymes of the TC-FDM family might already exist in nature or, at least, it would be feasible to design in vitro such monocomponent monooxygenase by protein engineering (unpublished data).…”
Section: Resultsmentioning
confidence: 99%
“…Flavodiiron proteins (FDPs), originally known as A-type flavoproteins (Flv) (Wasserfallen et al, 1998), function in detoxification of O 2 and/or NO in many strict and facultative anaerobes (Vicente et al, 2008a). FDPs form a complex group of enzymes, and many of them have been thoroughly characterized.…”
Section: Introductionmentioning
confidence: 99%
“…Flavodiiron proteins (FDPs), originally called A-type flavoproteins or Flvs (Wasserfallen et al, 1998), were recently demonstrated to have an important role in photoprotection of the photosynthetic machinery (Zhang et al, 2009Allahverdiyeva et al, 2011Allahverdiyeva et al, , 2013Ermakova et al, 2013). FDPs in general are most widespread among strict and facultative anaerobic bacteria.…”
mentioning
confidence: 99%